2021
DOI: 10.3389/fnagi.2021.659898
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Neurofilament Light Chain Is Not a Diagnostic Biomarker for Neurodegeneration in a Mixed Memory Clinic Population

Abstract: Neurodegeneration and axonal injury result in an increasing release of neurofilament light chain (NfL) into bodily fluids, including cerebrospinal fluid (CSF) and blood. Numerous studies have shown that NfL levels in CSF and blood are increased in neurodegenerative disorders and monitor neurodegeneration. Saliva is an easily accessible biofluid that could be utilized as a biofluid measurement of Alzheimer’s disease (AD) biomarkers. In this study, for the first time, salivary NfL was measured and compared to pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…In plasma and CSF, NfL has been shown to be a promising biomarker for neurodegeneration. However, a similar trend has not been found using saliva samples [ 18 ].…”
Section: Resultssupporting
confidence: 50%
“…In plasma and CSF, NfL has been shown to be a promising biomarker for neurodegeneration. However, a similar trend has not been found using saliva samples [ 18 ].…”
Section: Resultssupporting
confidence: 50%
“…Dementia diagnostics and biomarkers are highly developing fields and represents fruitful domains for new biomarkers, new sources to sample biomarkers [23,24], new technologies and the complex process of the clinical evaluation of a patient with a suspected dementia disorder. Better exploitation of already validated biomarkers is important for optimizing the diagnostic procedure, making it cost-effective and lessen the need for additional clinical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies report total protein in saliva from individuals with MCI or AD. Three recent studies show a trend of increasing total protein in saliva from individuals diagnosed with MCI or AD ( Galindez et al, 2021 ; Gleerup et al, 2021a , b ). Higher levels of salivary protein have also been reported in saliva from individuals with Parkinson’s disease (PD) ( Devic et al, 2011 ; Al-Nimer et al, 2014 ; Kang et al, 2014 ; Fedorova et al, 2015 ; Masters et al, 2015 ; Galindez et al, 2021 ) and have been attributed to reduced saliva flow ( Fedorova et al, 2015 ) and PD related salivary gland dysfunction ( Masters et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, levels of the amyloid-β (1–42) peptide have been shown to increase in AD saliva ( Bermejo-Pareja et al, 2010 ; Kim et al, 2014 ; Lee et al, 2017 ; Sabbagh et al, 2018 ; Katsipis et al, 2021 ), in contrast to the pattern of reduced levels observed in AD blood ( Nakamura et al, 2018 ). Other promising AD biomarkers detected in saliva include glial fibrillary acidic protein ( Katsipis et al, 2021 ), lactoferrin ( Carro et al, 2017 ; González-Sánchez et al, 2020 ; Gleerup et al, 2021a ; Reseco et al, 2021 ) and neuronal damage marker, neurofilament light chain ( Gleerup et al, 2021b ; Monroe et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%